SLE strikes the heart! A rare presentation of SLE myocarditis presenting as cardiogenic shock - Raval, Jaydeep J. (BMC Cardiovasc Disord, 2021)
BACKGROUND: Although systemic lupus erythematosus (SLE) can affect the cardiovascular system in many ways with diverse presentations, a severe cardiogenic shock secondary to SLE myocarditis is infrequently described in the medical literature. Variable presenting features of SLE myocarditis can also make the diagnosis challenging. This case report will allow learners to consider SLE myocarditis in the differential and appreciate the diagnostic uncertainty. CASE PRESENTATION: A 20-year-old Filipino male presented with acute dyspnea, pleuritic chest pain, fevers, and diffuse rash after being diagnosed with SLE six months ago and treated with hydroxychloroquine. Labs were notable for leukopenia, non-nephrotic range proteinuria, elevated cardiac biomarkers, inflammatory markers, low complements, and serologies suggestive of active SLE. Broad-spectrum IV antibiotics and corticosteroids were initiated for sepsis and SLE activity. Blood cultures were positive for MSSA with likely skin source. An electrocardiogram showed diffuse ST-segment elevations without ischemic changes. CT chest demonstrated bilateral pleural and pericardial effusions with dense consolidations. Transthoracic and transesophageal echocardiogram demonstrated reduced left ventricular ejection fraction (LVEF) 45% with no valvular pathology suggestive of endocarditis. Although MSSA bacteremia resolved, the patient rapidly developed cardiopulmonary decline with a repeat echocardiogram demonstrating LVEF < 10%. A Cardiac MRI was a nondiagnostic study to elucidate an etiology of decompensation given inability to perform late gadolinium enhancement. Later, cardiac catheterization revealed normal cardiac output with non-obstructive coronary artery disease. As there was no clear etiology explaining his dramatic heart failure, endomyocardial biopsy was obtained demonstrating diffuse myofiber degeneration and inflammation. These pathological findings, in addition to skin biopsy demonstrating lichenoid dermatitis with a granular “full house” pattern was most consistent with SLE myocarditis. Furthermore, aggressive SLE-directed therapy demonstrated near full recovery of his heart failure. CONCLUSION: Although myocarditis during SLE flare is a well-described cardiac manifestation, progression to cardiogenic shock is infrequent and fatal. As such, SLE myocarditis should be promptly considered. Given the heterogenous presentation of SLE, combination of serologic evaluation, advanced imaging, and myocardial biopsies can be helpful when diagnostic uncertainty exists. Our case highlights diagnostic methods and clinical course of a de novo presentation of cardiogenic shock from SLE myocarditis, then rapid improvement.